A study of pre- and post-treatment hematologic markers of immune response in patients undergoing radiotherapy for soft tissue sarcoma - Ku, Eric; Harada, Garrett; Lee, Grace; Munjal, Akul; Peterson, Nicholas; Park, Jino; Chow, Warren; Stitzlein, Russell; Limoli, Charles; Harris, Jeremy (Frontiers in Oncology, 2024)
IntroductionThis study investigates the impact of pre- and post-treatment hematologic markers, specifically neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR), on treatment outcomes in soft tissue sarcoma (STS) patients undergoing radiation therapy (RT).MethodsData from 64 patients who underwent RT for curative management of STS were reviewed. Pre-RT and post-RT hematologic measures were evaluated for associations with survival outcomes. A normal tissue complication probability (NTCP) curve for predicting ΔPLR ≥ 75 was modeled using a probit function.ResultsElevated baseline NLR was associated with worse overall survival (OS) and disease-free survival (DFS), while elevated PLR was associated with worse DFS. Post-RT, elevated PLR was linked to worse OS and DFS. Increasing PLR change post-RT was associated with worse OS and DFS. Receiver operating characteristics analysis determined ΔPLR ≥ 75 to be a robust cutoff associated with worse DFS. Bone V10Gy ≥362 cc corresponded to a 50% risk of developing ΔPLR ≥ 75.DiscussionThese results suggest that hematologic markers could serve as prognostic biomarkers in both pre- and post-treatment settings for STS patients undergoing RT. Future studies can consider using bone V10Gy < 362 cc as a potential cutoff to reduce the risk of increased PLR after RT.